Molecular Characteristics of Scylla paramamosain Ubiquitin-Conjugating Enzyme E2 and Expression Analysis During Oogenesis - Han, Kunhuang; Dai, Yanbin; Zhang, Ziping; Rao, Congwen; Zhou, Li; Wang, Yilei (Frontiers in Marine Science, 2022)
Ubiquitination is an essential post-translational modification of proteins and involved in many physiological processes, including sperm differentiation, oocyte maturation and embryonic development. And the ubiquitin-conjugating enzyme E2 play crucial role in gametogenesis. However, the E2 participate in regulation of crustaceans gonad development is still very limited, especially for oogenesis. In this research, we isolated and identified full-length Sp-Ubc2 cDNA from green mud crab (Scylla paramamosain), detected distribution in different tissues by RT-qPCR and described expression patterns during oogenesis by in situ hybridization. The results demonstrated that the deduced Sp-Ubce2 proteins with UBC catalytic domain was clustered with other arthropods. And the Sp-Ubc2 widely distributed in different tissues of female individuals and kept highest expression level in ovary. Moreover, the expression level of Sp-Ubc2 changed significantly during oogenesis, and reached peak in mid- and late- vitellogenesis stages. the expression level of Sp-Ubc2 reached its peak. At the same time, the Sp-Ubc2 signal in ovary gradually concentrated in nuclei. These results indicated that Sp-Ubc2 might play important roles in cell cycle of oogenesis. This study would provide insights into the regulatory mechanism of gonad development in S. paramamosain under farmed conditions.